Effect of Waveform on Tactile Perception by Electrovibration Displayed on Touch Screens - Vardar, Yasemin; Guclu, Burak; Basdogan, Cagatay (IEEE transactions on haptics, 2017)
In this study, we investigated the effect of input voltage waveform on our haptic perception of electrovibration on touch screens. Through psychophysical experiments performed with eight subjects, we first measured the detection thresholds of electrovibration stimuli generated by sinusoidal and square voltages at various fundamental frequencies. We observed that the subjects were more sensitive to stimuli generated by square wave voltage than sinusoidal one for frequencies lower than 60 Hz. Using Matlab simulations, we showed that the sensation difference of waveforms in low fundamental frequencies occurred due to the frequency-dependent electrical properties of human skin and human tactile sensitivity. To validate our simulations, we conducted a second experiment with another group of eight subjects. We first actuated the touch screen at the threshold voltages estimated in the first experiment and then measured the contact force and acceleration acting on the index fingers of the subjects moving on the screen with a constant speed. We analyzed the collected data in the frequency domain using the human vibrotactile sensitivity curve. The results suggested that Pacinian channel was the primary psychophysical channel in the detection of the electrovibration stimuli caused by all the square-wave inputs tested in this study. We also observed that the measured force and acceleration data were affected by finger speed in a complex manner suggesting that it may also affect our haptic perception accordingly.